The Employment of Ahl al-Dhimma During the Mamluk Era (648-923/1250-1517) - Eser, Mehmet Emin (Near East University, 2023)
The Mamluks, who ruled in Egypt and Syria between 648/1250 and 923/1517, were a Turkish state established by Turkish-origin people who were taken as slaves and eventually took over the administration. During the Mamluk period, Christians and Jews were accepted by both the state and society. These minorities were an integral part of Mamluk society and were subject to social, political, economic, and intellectual life like other members of society. At times, they were assigned various positions in the government, while at other times, they were dismissed from their duties due to undesirable events and faced employment bans. The administrative experiences of non-Muslims in the government were effective in their assignments to various levels of the state during the Mamluk period. Thus, non-Muslims were continuously employed in administrative and financial positions of the state during the Mamluk period. Although it was said that the most prestigious position that non-Muslims could achieve in the government administration was the position of a clerk, non-Muslims were assigned to top positions in the state from the early period of the Mamluks. During this period, non-Muslims were employed in positions such as vizier and governorship, as well as clerks, interpreters, advisors, doctors, and ambassadors. In fact, during the reign of Sultan Aybek (648-784/1250-1257), his vizier, Şerefüddin, was a Christian. He preferred to assign Christians to important financial positions in the state using his position as vizier. Thus, Christians became privileged in Mamluk society during this period. It is also stated that because Vezir Şerefüddin is an intellectual, he writes the laws of the state. Later, during the reign of Sultan al-Nasir Muhammad b. Qalawun (709-741/1309-1341), a Coptic Christian named Abdullah b. Taj al-Riyasah was employed as a vizier both in Damascus and Egypt. Additionally, due to their ability to speak different languages, non-Muslims served as translators in international diplomacy and trade as well as serving as ambassadors. During the reign of Sultan el-Melikü’l-Eşref Barsbay, the traveler Pero Tafur, who visited Egypt, stated that the Sultan's interpreter was a non-Muslim named Haym who later took on a different name when he converted to Islam. Similarly, it is known that a person named Nasreddin, who came to Jerusalem from Spain in 1420 and worked as a translator here and later became a Muslim, is a person of Jewish origin. In the same way, during the reign of Sultan al-Meliku'l-Ashraf Kansu Gavri, Yakup, who was a teacher from the ahl al-zim, was appointed head of the mint. In this sense, it is understood that under Mamluk rule, Jews were employed not only in the financial and economic fields but also in areas such as translation and clerical work. Medicine and money-changing also held an important place among Jewish professions during that period. Sources from the 7th century AH indicate that "tax collection and medicine were the most important sources of income for Jews and Christians." During this period, the medical profession was generally associated with Jews. They were able to exert influence over the palace and the royal authority through this profession. This also led to an increase in the reputation of the Jewish community among society. Therefore, those who lived under the administration of the Mamluk state, generally in the zimmî status, and specifically Jews and Christians, were always part of the Mamluk population and were assigned to different levels of the state. Non-Muslims who were appointed within the state were sometimes dismissed from their duties, but some of them were returned to their duties with dignity after a while.

648/1250 - 923/1517 yılları arasında Mısır ve Suriye’de hüküm süren Memlükler köle olarak alınan Türk kölelerin, zamanla yönetimi ele geçirmesi ile kurulmuş bir Türk devletidir. Memlükler döneminde Hıristiyanlar ve Yahudiler hem devlet tarafından hem de toplum tarafından kabul görmüşlerdir. Bu azınlıklar, Memlük toplumunda, toplumun diğer bireyleri gibi sosyal, politik, ekonomik ve entelektüel hayatın ayrılmaz bir parçasıydılar. Kimi zaman bunlar devletin çeşitli kademelerinde görevlendirilmişler, kimi zaman da yaşanılan olaylar sebebiyle görevlerinden alınarak kendilerine istihdam yasağı getirilmiştir. Gayrimüslimlerin devlet idaresindeki tecrübeleri onların devletin değişik kademelerinde görevlendirmelerinde etkili olmuştur. Böylece Memlükler döneminde gayrimüslimler, devlet idaresindeki idarî ve malî kadrolarda devamlı istihdam edilmişlerdir. Gayrimüslim halkın devlet idaresinde gelebilecekleri en muteber makamın kâtiplik olduğu söylenmesine rağmen, gayrimüslimler Memlüklerin ilk döneminden itibaren devletin üst kademelerinde de görevlendirilmişlerdir. Bu dönemde gayrimüslimlerin vezirlik ve valilik başta olmak üzere kâtiplik, tercümanlık, danışmanlık, tabiplik, elçilik gibi vazifelerde istihdam edildikleri görülmektedir. Nitekim Sultan Aybek (648-784/1250-1257) döneminde görevde bulunan Vezir Şerefüddin Hıristiyan biri idi. Bu kişi vezirlik konumunu kullanarak devletin çok önemli malî kadrolarında Hıristiyanların görevlendirilmesine vesile olmuştur. Böylece bu dönemde Hristiyanlar Memlük toplumunda ayrıcalıklı hale gelmiştir. Ayrıca Vezir Şerefüddin entelektüel biri olması sebebiyle, devletin kanunlarını yazdığı da belirtilmektedir. Daha sonra Sultan en-Nâsır Muhammed b. Kalavun (709-741/1309-1341) döneminde Kıptî bir Hıristiyan olan Abdullah b. Tâcürriyâse hem Şam hem de Mısır’da vezirlik görevinde istihdam edilmiştir. Bununla beraber gayrimüslimler, farklı dilleri konuşabilmeleri sebebiyle Memlükler idaresinde uluslararası diplomasi ve ticarette tercümanlık yaptıkları gibi sefirlik/elçilik de yapmışlardır. Sultan el-Melikü’l-Eşref Barsbay’ın saltanatı sırasında Mısır’ı ziyaret eden seyyah Pero Tafur, sultanın tercümanının Haym isminde bir gayrimüslim olduğunu, daha sonra Müslüman olduğunda farklı bir isim aldığını belirtmiştir. Benzer şekilde 823/1420 yılında İspanya’dan Kudüs’e gelip burada mütercimlik yapan ve daha sonra Müslüman olan Nasreddin adındaki şahsın Yahudi kökenli biri olduğu bilinmektedir. Aynı şekilde Sultan el-Melikü’l-Eşref Kansu Gavrî döneminde ehl-i zimmeden bir öğretmen olan Yakup, darphanenin başına getirilmiştir. Bu anlamda Memlükler idaresinde Yahudilerin de malî ve ekonomik alanların yanı sıra mütercimlik, kâtiplik ve benzeri alanlarda istihdam edildikleri anlaşılmaktadır. Hekimlik ve sarraflık da o dönem Yahudi meslekleri arasında önemli bir yer işgal etmiştir. H. 7. yüzyıla ait kaynaklar, “Yahudi ve Hristiyanlar için en önemli gelir kaynağının vergi tahsilatı ve tababet/doktorluk” olduğunu belirtmektedirler. Bu dönemde doktorluk, genel anlamda Yahudilerle anılmaktaydı. Onlar bu meslek sayesinde saray ve saray otoritesi üzerinde söz sahibi olabiliyorlardı. Bu da Yahudi cemaatinin toplum nezdindeki itibarının yükselmesine neden oluyordu. Dolayısıyla Memlük Devleti’nin idaresi altında yaşayan genelde zimmî statüsünde olanlar özelde ise Yahudi ve Hıristiyanlar Memlük ahalisinin her zaman bir parçası durumunda olup devletin farklı kademelerinde görevlendirilmişlerdir. Devlet içinde görevlendirilen gayrimüslimler, kimi zaman görevlerinden azl edilmişlerse de bunlardan bazıları bir süre sonra tekrar itibarlı bir şekilde görevlerine iade edilmişlerdir.
Memlükler Döneminde (648-923/1250-1517) Ehl-i Zimme’nin İstihdamı
Keywords: History of Islam; İslam Tarihi